Smoking, inflammatory patterns and postprandial hypertriglyceridemia - Kabagambe, Edmond K. (2008)
BACKGROUND: Smoking is associated with increased postprandial hypertriglyceridemia (PPT). Inflammation and insulin resistance are potential “drivers” for this phenomenon. We tested whether inflammatory patterns and/or insulin resistance explain the effect of smoking on PPT. METHODS AND RESULTS: Men and women in the NHLBI Genetics of Lipid-Lowering Drugs and Diet Network (GOLDN) study (n=1036, age 49±16 y) were included. Each participant was asked to suspend use of lipid-lowering drugs for three weeks and was given a high-fat milkshake (83% fat and 700 kcal/m(2)). Triglyceride concentrations at 0, 3.5 and 6 hr after the fat load were measured. Inflammatory markers were measured at baseline. Principal component analysis was used to derive inflammatory patterns from individual inflammatory markers (hsCRP, IL2 soluble receptor-α, IL6, TNF-α and MCP-1). Insulin resistance (IR) was estimated using the HOMA equation. Repeated measures-ANOVA was used for analyses. Two inflammatory patterns, namely CRP-IL6 pattern and MCP1-TNF-α pattern, were derived. We found significant main (smoking and time) and interaction (smoking*time) effects (P<0.01) for triglycerides. The multivariate-adjusted triglyceride (mg/dl) concentrations (mean ± s.e.m) for never, past and current smokers were 127.38±1.04, 119.82±1.05 and 134.92±1.08 at 0 hr; 229.42±1.04, 238.39±1.05 and 293.94±1.08 at 3.5 hr; and 194.63±1.04, 208.38±1.05 and 248.27±1.08 at 6 hr after the fat load, respectively. Smoking remained significant after adjusting for HOMA-IR and/or inflammatory patterns which showed independent associations with PPT (P<0.05). CONCLUSIONS: These data confirm impaired metabolism of fat among smokers and suggest that mechanisms other than inflammation or insulin resistance may explain the observed hypertriglyceridemia among smokers.